Micropatterning of metal nanoparticle ink by laser-induced thermocapillary flow - Park, Sewoong; Kwon, Jinhyeong; Lim, Jaemook; Shin, Wooseop; Lee, Younggeun; Lee, Habeom; Kim, Hyun Jong; Han, Seungyong; Yeo, Junyeob; Ko, Seung Hwan; Hong, Sukjoon (Nanomaterials, 2018)
Selective laser sintering of metal nanoparticle ink is a low-temperature and non-vacuum technique developed for the fabrication of patterned metal layer on arbitrary substrates, but its application to a metal layer composed of large metal area with small voids is very much limited due to the increase in scanning time proportional to the metal pattern density. For the facile manufacturing of such metal layer, we introduce micropatterning of metal nanoparticle ink based on laser-induced thermocapillary flow as a complementary process to the previous selective laser sintering process for metal nanoparticle ink. By harnessing the shear flow of the solvent at large temperature gradient, the metal nanoparticles are selectively pushed away from the scanning path to create metal nanoparticle free trenches. These trenches are confirmed to be stable even after the complete process owing to the presence of the accompanying ridges as well as the bump created along the scanning path. As a representative example of a metal layer with large metal area and small voids, dark-field photomask with Alphabetic letters are firstly created by the proposed method and it is then demonstrated that the corresponding letters can be successfully reproduced on the screen by an achromatic lens.
Keywords: Laser-induced thermocapillary flow; Metal nanoparticle ink; Selective laser sintering